The role of health literacy in the association between social support and self-rated health: a Danish population-based study in 10,787 individuals with a long-term condition - Anne-Sofie Meldgaard Nielsen; Helle Terkildsen Maindal; Gitte Valentin (BMC, 2024)
Abstract Background Managing a long-term condition requires higher health literacy. Social networks may play a crucial role for self-management. However, the pathway is not entirely understood. This study aimed to examine whether the association between social support and self-rated health is mediated by health literacy among individuals with a long-term condition. Methods This cross-sectional study used data from the "How are you?" 2021 survey in Central Denmark Region. Social support was assessed using a single question, health literacy with two dimensions from the Health Literacy Questionnaire (HLQ): 'Understanding health information' and 'Engaging with healthcare providers', and self-rated health with a single question from SF-36. Multiple logistic regression analyses were used to examine the associations, and multiple mediation analyses were performed using the Karlson-Holm-Breen method. Results A total of 10,787 individuals with a long-term condition were included in the study, whereas 6% (n = 595) reported a low level of social support. Both health literacy scales mediated the association between social support and self-rated health, particularly the ability to engage with healthcare providers, accounting for 25% of the variance. After adjustment for sociodemographic factors, individuals with a low level of social support had significantly higher odds of reporting difficulties in understanding health information (OR 2.53 (95% CI: 1.84-3.48)) and engaging with healthcare providers (OR 3.77 (95% CI: 2.96-4.79)). Conclusions Health literacy, particularly the ability to engage with healthcare providers, was a mediator between social support and self-rated health. Additionally, a low level of social support was associated with higher odds of reporting lower health literacy. These findings suggest that strategies to enhance health literacy, improve health outcomes, and reduce health inequities may benefit from strengthening individuals' social network, particularly focusing on those with limited support.